IMPLEMENTATION OF KLAGENSRAMPAT SDN GROUP GUIDANCE SERVICES IN THE INDEPENDENT CURRICULUM - Diyah Rahmawati; Alfu Salsabilla R. (Universitas Muhammadiyah Lamongan, 2024)
The background to the implementation of group guidance services at SDN Klagensrampat in the independent curriculum is useful for developing students' personal potential, and can also influence students' talents and interests to be further developed optimally. The aim of this research is that the Klagensrampat Elementary School group guidance service in the independent curriculum is useful for finding out how the implementation of counseling guidance at Kagensrampat Elementary School in the independent curriculum is useful for finalizing achievements in developing self-potential in these students. The method used in this research is descriptive qualitative. The data source for this research is class 1 teachers. The instruments used are teacher interviews and teacher observations, namely using group guidance services. The Click or tap here to enter text.results of this research are (1) group guidance services in developing students' interests, talents, (2) handling of counseling by teachers using guidance. groups, (3) use of group guidance services by teachers. The conclusion of this research is that teachers provide group guidance to help students in the learning process and develop the potential of students' interests and talents.